2018
DOI: 10.1080/00365521.2018.1498120
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic mucosal resection with suction vs. endoscopic submucosal dissection for small rectal neuroendocrine tumors: a meta-analysis

Abstract: The present meta-analysis mostly based on retrospective studies show that EMR with suction is superior to ESD for small rectal NETs (≤10 mm) with higher complete resection rate, shorter procedure time, and similar overall complication rate and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
3
28
2
Order By: Relevance
“…In our retrospective dataset, both the en bloc and complete resection rates of ASEMR were not significantly different from those of EMR-C. Compared with the complete resection rate of EMR-C for small NETs found in our previous report (94.1%) 13 , and the pooled complete resection rate of EMR with suction methods for small NETs reported in a meta-analysis (93.7%) 15 , the complete resection rate of ASEMR for rectal NETs found in the current study seems acceptable. According to an earlier report on the ASEMR technique, the provision of gentle pressure toward the anchoring point helps the snare widen laterally while snaring and contributes to acquisition of a larger specimen size 18 .…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…In our retrospective dataset, both the en bloc and complete resection rates of ASEMR were not significantly different from those of EMR-C. Compared with the complete resection rate of EMR-C for small NETs found in our previous report (94.1%) 13 , and the pooled complete resection rate of EMR with suction methods for small NETs reported in a meta-analysis (93.7%) 15 , the complete resection rate of ASEMR for rectal NETs found in the current study seems acceptable. According to an earlier report on the ASEMR technique, the provision of gentle pressure toward the anchoring point helps the snare widen laterally while snaring and contributes to acquisition of a larger specimen size 18 .…”
Section: Discussioncontrasting
confidence: 61%
“…Our previous study on small rectal NETs indicated that EMR-C required a shorter procedure time than ESD, while the therapeutic efficacy and safety profiles did not significantly differ between the two procedures 13 . Furthermore, a recent meta-analysis suggested that EMR with suction (EMR-C or EMR-L) was superior to ESD for complete removal of small rectal NETs 15 . However, EMR with suction techniques requires specialized devices, such as a band ligation device for EMR-L and a suction cap with inner rim looped by a crescent-type snare for EMR-C. As these devices are essential for each procedure, endoscopists and assistants need to spend additional time and effort on applying the devices to the scope.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, R0 rates (89.5 % -94.1 %) were similar between mEMR and ESD [11,12]. In contrast, a recent meta-analysis showed that mEMR (with suction) is superior to ESD for small rectal NETs (≤ 10 mm) in terms of histological complete resection and procedure time [13].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies on rectal NETs showed that the complete resection rate was significantly higher after ESD relative to simple EMR but was comparable to modified EMR (EMR with banding or using a cap and suction) [ 19 , 28 ]. Surprisingly, other studies, including a meta-analysis on 14 studies and 823 cases, concluded that modified EMR with the suction method (93.65%) is superior to ESD (84.08%) in achieving free resection margins in rectal NETs smaller than 10 mm [ 29 31 ]. The modified EMR (m-EMR) technique using either suction cap or ligation band is much more effective in achieving complete resection and R0 margin comparing to conventional EMR procedure which is performed by a snare after submucosal saline injection [ 19 ].…”
Section: Discussionmentioning
confidence: 99%